2016
DOI: 10.1007/s13197-016-2207-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the effectiveness of ozonated water and peracetic acid in the storability of packaged fresh-cut melon

Abstract: Ozonated water and peracetic acid were tested as sanitizers to enhance the storability of fresh-cut melon cubes. Sanitizers were also combined with suitable packaging materials (polypropylene and polylactic acid based plastic films). Fresh-cut melon cubes were stored at 4°C for up to 7 days. Ozonated water and peracetic acid treatments were given by dipping cubes into 0.8 ppm O 3 and 100 ppm Tsunami 100™ solutions, respectively, for 3 min. Both sanitizers exhibited efficiency in reducing the total microbial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The L* and a* values also reflected no differences between the two conditions (data not shown). A uniform trend was also observed after 10 μL L −1 gaseous O 3 treatment of tomato fruits by Rodoni et al, 21 whereas Botondi et al 22 found that washing melon cubes with ozonised water induced a gradual decrease in colour (parameters L* and C*) during storage.…”
Section: Quality Parametersmentioning
confidence: 64%
See 2 more Smart Citations
“…The L* and a* values also reflected no differences between the two conditions (data not shown). A uniform trend was also observed after 10 μL L −1 gaseous O 3 treatment of tomato fruits by Rodoni et al, 21 whereas Botondi et al 22 found that washing melon cubes with ozonised water induced a gradual decrease in colour (parameters L* and C*) during storage.…”
Section: Quality Parametersmentioning
confidence: 64%
“…To date, there are very few bibliographical works dealing with melons that have been cut and washed with ozonised water, while there is only one by Selma et al . on whole and cut melons in which samples were exposed to 5000, 10 000 and 20 000 ppm O 3 at 11 °C and 90–95% RH for 30 min, followed by storage at 5 °C for up to 7 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other postharvest techniques, such as microwave, heating, ozonation, and controlled/modified atmosphere packaging, have been proposed as alternatives to replace the treatment of fruit with chemical fungicides. However, their negative impacts on fruit quality characteristics are considered drawbacks for a practical use (Aloui et al, 2014;Botondi, Moscetti, & Massantini, 2016;Castellanos, Mendoza, Gavara, & Herrera, 2017;Rodriguez & Zoffoli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial action of ozone can be due to the oxidation of the cellular vital components which causes the inhibition of the microbial development or indirectly through the defense mechanisms as a response of the plants [21]. Several studies have been carried out on the antimicrobial capacity of ozone and its effects on the quality of different products such as papaya [18], lettuce and spinach [20], fresh-cut melon [22] and fresh-cut apple [23]. In addition, other study has shown that gaseous ozone can have a positive effect on changes in the content of antioxidant components, e.g., flavonoids and other phenolic compounds [24,25].…”
Section: Introductionmentioning
confidence: 99%